Lokasi Rawan Kecelakaan (Blackspot) Pengaruh Alinyemen Jalan: Studi Kasus : Ruas Jalan Prof. Dr. Ir. Sutami Bandar Lampung - Miruyama; Rachmat Mudiyono; Juny Andry Sulistyo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The road that often has accidents on the uphill and downhill sections as well as sharp bends is the Prof. Dr. Ir. Sutami Road Section. This path is used by different types of vehicles, from small cars to heavy trucks making their way to the industrial area. In STA 0+000 to STA 1+200, accidents often occur because it has an uphill road contour with grades varying between 0.15% -12.61%. Referring to traffic accident data from 2015 to 2019, there have been occurrences leading to minor harm, major harm, and loss of life. For this reason, researchers need to analyze the causes of accidents, analyze road alignment, analyze how to overcome and prevent them. The approach employed involves collecting primary and secondary data, then evaluated together. The evaluation data show that the origins accident include human factors, where individuals panic when the brakes fail, vehicle factors related to operational unfitness, and road factors as the location is on a collector road with a VLHR of 13,000/SMP per day. With the presentation of trucks, 47% have a topography with a height difference of up to 39 meters at a distance of 695 meters. The results of the alignment analysis with a slope of almost 13% the slope value varies from 6% - 12% per 25 m and LOS C. How to overcome and prevent accidents are carried out safety driver training, operational vehicle regulations and. Improvement of road alignment with climbing lanes and rescue paths.